2021
DOI: 10.1007/s12325-021-01781-z
|View full text |Cite|
|
Sign up to set email alerts
|

A Framework for Estimating the Eligible Patient Population for New Migraine Acute Therapies in the United States

Abstract: Introduction: Migraine is associated with considerable disability for patients not adequately managed with current standards of care. New acute therapies may offer relief for this population of patients; however, population size and associated potential costs of new therapies are unclear. In this study, a conceptual framework was developed to estimate anticipated use of new acute therapies. Methods: Targeted literature review (TLR) was conducted to identify factors affecting access to migraine-specific acute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…This analysis of prescription data for Medicaid enrollees with FFS coverage in 2020 showed that approximately 20% of migraine-specific acute therapy prescriptions were for formulations other than generic triptan tablets. This estimate is consistent with previous research in the USA [37] and England [38] as well as with a US budget impact analysis of new acute therapies May require an extra dose or rescue medication [44][45][46][47] b 1 unit per 24 h [48] c 1 unit per month [49][50][51] d 1 unit (30-min infusion) per 3 months [52] Adv Ther [39] conducted in 2019 by the Institute for Clinical and Economic Review, suggesting that 15-25% of patients with migraine may progress beyond first-line migraine-specific acute treatments. Per-unit cost estimates based on Medicaid amounts reimbursed indicated that, among migraine-specific acute therapies, intranasal DHE is the most expensive followed by injectable DHE, injectable triptans, gepants (rimegepant, ubrogepant) and lasmiditan, intranasal triptans, other oral ergotamine-based therapies, and oral triptans.…”
Section: Discussionsupporting
confidence: 94%
“…This analysis of prescription data for Medicaid enrollees with FFS coverage in 2020 showed that approximately 20% of migraine-specific acute therapy prescriptions were for formulations other than generic triptan tablets. This estimate is consistent with previous research in the USA [37] and England [38] as well as with a US budget impact analysis of new acute therapies May require an extra dose or rescue medication [44][45][46][47] b 1 unit per 24 h [48] c 1 unit per month [49][50][51] d 1 unit (30-min infusion) per 3 months [52] Adv Ther [39] conducted in 2019 by the Institute for Clinical and Economic Review, suggesting that 15-25% of patients with migraine may progress beyond first-line migraine-specific acute treatments. Per-unit cost estimates based on Medicaid amounts reimbursed indicated that, among migraine-specific acute therapies, intranasal DHE is the most expensive followed by injectable DHE, injectable triptans, gepants (rimegepant, ubrogepant) and lasmiditan, intranasal triptans, other oral ergotamine-based therapies, and oral triptans.…”
Section: Discussionsupporting
confidence: 94%
“…It can be relieved after rest and aggravated after activity. If treated inactively or improperly, headache severity may progress throughout an attack and even develop into chronic migraine [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine is divided into episodic (< 15 monthly headache days, MHDs) and chronic (≥ 15 MHDs, with migraine attacks occurring at least 8 days per month), according to the frequency of headache days per month [ 2 ]. In the 2016 Global Burden of Disease Study, migraine was a leading cause of disability among patients under 50 years of age worldwide, second only to lower back pain [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These therapies are currently recommended for use in adult patients with insufficient response to 2 or more triptans, or for those who experience intolerable side effects or have contraindications to triptans 5. A targeted literature review found that 15% to 25% of patients with migraine fulfill these requirements and may be eligible for rimegepant, ubrogepant or lasmiditan 7…”
mentioning
confidence: 99%
“…5 A targeted literature review found that 15% to 25% of patients with migraine fulfill these requirements and may be eligible for rimegepant, ubrogepant or lasmiditan. 7 These CGRP receptor antagonists reduce pain and inflammation and have fewer adverse events than older treatments due to their mechanism of action, [8][9][10] and they have no apparent association with medication overuse headache. 5 Ubrogepant is currently approved by the US Food and Drug Administration (FDA) for the acute treatment of migraine in adults, and rimegepant is a dual-use therapy approved for both acute and preventive treatment.…”
mentioning
confidence: 99%